IoT enabled adaptive clustering based energy efficient routing protocol for wireless sensor networks. (25th September 2019) - Asad, Muhammad; Aslam, Muhammad; Nianmin, Yao; Ayoub, Naeem; Qureshi, Khalid Ibrahim; Munir, Ehsan Ullah
In this paper, we propose a new internet of things (IoT) enabled multi adaptive clustering (MAC) energy efficient routing protocol for wireless sensor networks (WSNs) to minimise energy dissipation and improve the network performance. This new technique holds the hybrid cluster formation algorithm in which the network topology is divided in two regions where the first region is centralised and the second region is distributed. Both regions contain homogeneous and heterogeneous nodes while the sink is static and located in the centre of both networks. Specifically, proposed IoT enabled MAC routing protocol holds the major three properties: enabling of resources to sensor nodes through IoT, hybrid cluster formation to distribute the network load evenly among sensor nodes and a new mechanism to minimise the energy consumption in long range data transmission. In all of our experiments MAC achieves greater performance than state-of-the-art routing protocols. Moreover, performance evaluation proofs that MAC outperforms in critical network environment.